Do the microorganisms from laboratory culture spent growth medium affect house dust mite fitness and microbiome composition? - Molva, Vít; Bostlová, Marie; Nesvorná, Marta; Hubert, Jan (Insect science, 2020)
The interaction of house dust mites (HDM) and microorganisms is the key factor in the survival of these mites in human-made environments. Spent growth medium (SPGM) provides the rest of the diet, along with dead mite bodies and microorganisms. SPGM represents a source of microorganisms for the recolonization of mite food and the mite digestive tract. An experiment was performed to observe how adding SPGM to the HDM diet affects HDM population growth, the microbiome composition and the microbial respiration in microcosms. We analyzed American house dust mite (Dermatophagoides farinae) and European house dust mite (Dermatophagoides pteronyssinus) originating from control diets and diets treated with an extract of SPGM from 1- and 3-month-old mite cultures. The microbiome was described using 16S and 18S barcode sequencing. The composition of the bacterial and fungal microbiomes differed between the HDM species, but the SPGM treatment influenced only the bacterial profile of D. farinae. In the D. farinae microbiome of specimens on SPGM-treated diets compared to those of the control situation, the Lactobacillus profile decreased, while the Cardinium, Staphylococcus, Acinetobacter, and Sphingomonas profiles increased. The addition of SPGM extract decreased the microbial respiration in the microcosms with and without mites in almost all cases. Adding SPGM did not influence the population growth of D. farinae, but it had a variable effect on D. pteronyssinus. The results indicated that the HDM are marginally influenced by the microorganisms in their feces.
Keywords: mikrobiota; Culture Media; Population Growth; Animals; mužské pohlaví; ženské pohlaví; Genetic Fitness; zvířata; Female; Dermatophagoides pteronyssinus; Male; Microbiota; genetická zdatnost; populační růst; kultivační média